Cities in a sunburnt country water and the making of urban Australia - Cook, Margaret 1968- (Studies in environment and history, 2022)
As Australian cities face uncertain water futures, what insights can the history of Aboriginal and settler relationships with water yield? Residents have come to expect reliable, safe, and cheap water, but natural limits and the costs of maintaining and expanding water networks are at odds with forms and cultures of urban water use. Cities in a Sunburnt Country is the first comparative study of the provision, use, and social impact of water and water infrastructure in Australia's five largest cities. Drawing on environmental, urban, and economic history, this co-authored book challenges widely held assumptions, both in Australia and around the world, about water management, consumption, and sustainability. From the 'living water' of Aboriginal cultures to the rise of networked water infrastructure, the book invites us to take a long view of how water has shaped our cities, and how urban water systems and cultures might weather a warming world